2003
DOI: 10.1080/02786820300914
|View full text |Cite
|
Sign up to set email alerts
|

Determining Size-Specific Emission Factors for Environmental Tobacco Smoke Particles

Abstract: Because size is a major controlling factor for indoor airborne particle behavior, human particle exposure assessments will benefit from improved knowledge of size-specific particle emissions. We report a method of inferring size-specific mass emission factors for indoor sources that makes use of an indoor aerosol dynamics model, measured particle concentration time series data, and an optimization routine. This approach provides-in addition to estimates of the emissions size distribution and integrated emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
1
9

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 28 publications
2
81
1
9
Order By: Relevance
“…Cigarette emissions Although many studies have calculated particle mass emissions from cigarettes, few have provided number emission rates (Klepeis et al, 2003). In one experiment, a single Marlboro cigarette was smoked in the kitchen of the Virginia town house on 24 December 1997.…”
Section: Exposures In Homesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cigarette emissions Although many studies have calculated particle mass emissions from cigarettes, few have provided number emission rates (Klepeis et al, 2003). In one experiment, a single Marlboro cigarette was smoked in the kitchen of the Virginia town house on 24 December 1997.…”
Section: Exposures In Homesmentioning
confidence: 99%
“…Outdoor UFP concentrations were measured for 1-2 years in several US cities (U.S. EPA Supersites program; Solomon et al, 2008), and near roadways in California (Zhu et al, 2002) and also in Erfurt and Augsberg, Germany (Wichmann et al, 2000). Residential indoor concentrations have also been reported (Abt et al, 2000;Dennekamp et al, 2001;Long et al, 2001;Wallace and Howard-Reed, 2002;Klepeis et al, 2003;He et al, 2004;Wallace, 2000Wallace, , 2005Wallace, , 2006Wallace et al, 2004Wallace et al, , 2008Hoek et al, 2008). A number of studies of exposures while driving have been done (Westerdahl et al, 2005;Fruin et al, 2008;Zhu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We did not differentiate by particle size or incorporate particle deposition in the lung. Gravimetrically determined values for total SHS particle emission factors reported in the literature for cigarettes are in the approximate range of 8−20 mg cig −1 (see Klepeis et al, 2003). We chose 10 mg cig −1 to represent typical SHS particle emissions from a cigarette and 50 mg cig −1 to represent typical cigarette CO emissions (Martin et al, 1997).…”
Section: Emissions and Smoker Characteristicsmentioning
confidence: 99%
“…A TSI 2.5-mm-size impactor was installed at the intake of each SidePak monitor, which can measure particles down to a diameter of 0.1 mm (TSI, 2013a). Although the size range of secondhand smoke particles is 0.02-2 mm, about 90% of the particle mass is between 0.1 and 0.5 mm (Klepeis et al, 2003). Jiang et al (2011) found a consistent relationship between the SidePak readings and known mass concentrations of tobacco smoke measured using a gravimetric, pump-driven sampler with filters weighted on a precision laboratory scale.…”
Section: Instruments and Measurementsmentioning
confidence: 99%